Low complexity regions in the proteins of prokaryotes perform important functional roles and are highly conserved. Issue 19 (4th September 2019) - Ntountoumi, Chrysa; Vlastaridis, Panayotis; Mossialos, Dimitris; Stathopoulos, Constantinos; Iliopoulos, Ioannis; Promponas, Vasilios; Oliver, Stephen G; Amoutzias, Grigoris D
Abstract: We provide the first high-throughput analysis of the properties and functional role of Low Complexity Regions (LCRs) in more than 1500 prokaryotic and phage proteomes. We observe that, contrary to a widespread belief based on older and sparse data, LCRs actually have a significant, persistent and highly conserved presence and role in many and diverse prokaryotes. Their specific amino acid content is linked to proteins with certain molecular functions, such as the binding of RNA, DNA, metal-ions and polysaccharides. In addition, LCRs have been repeatedly identified in very ancient, and usually highly expressed proteins of the translation machinery. At last, based on the amino acid content enriched in certain categories, we have developed a neural network web server to identify LCRs and accurately predict whether they can bind nucleic acids, metal-ions or are involved in chaperone functions. An evaluation of the tool showed that it is highly accurate for eukaryotic proteins as well.